Dual Inhibition of FLT3 and AXL by Gilteritinib Overcomes Hematopoietic Niche-Driven Resistance Mechanisms in FLT3 -ITD Acute Myeloid Leukemia - Dumas, Pierre-Yves; Villacreces, Arnaud; Guitart, Amélie V.; El-habhab, Ali; Massara, Layal; Mansier, Olivier; Bidet, Audrey; Martineau, Delphine; Fernandez, Solene; Leguay, Thibaut; Pigneux, Arnaud; Vigon, Isabelle; et al. (Clinical cancer research, 2021)
AXL has been shown to play a pivotal role in the selective response of -ITD acute myeloid leukemia (AML) cells to FLT3 tyrosine kinase inhibitors (TKI), particularly within the bone marrow microenvironment. Herein, we compared the effect of dual FLT3/AXL-TKI gilteritinib with quizartinib through models mimicking hematopoietic niche conditions, in primary AML blasts, and with dosing regimens allowing plasma concentration close to those used in clinical trials. We observed that gilteritinib maintained a stronger proapoptotic effect in hypoxia and coculture with bone marrow stromal cells compared with quizartinib, linked to a dose-dependent inhibition of AXL phosphorylation. , use of the MV4-11 cell line with hematopoietic engraftment demonstrated that gilteritinib was more effective than quizartinib at targeting leukemic cells in bone marrow. Finally, -ITD AML patient-derived xenografts revealed that this effect was particularly reproducible in -ITD AML with high allelic ratio in primary and secondary xenograft. Moreover, gilteritinib and quizartinib displayed close toxicity profile on normal murine hematopoiesis, particularly at steady state. Overall, these findings suggest that gilteritinib as a single agent, compared with quizartinib, is more likely to reach leukemic cells in their protective microenvironment, particularly AML clones highly dependent on -ITD signaling.